KEPUASAN NASABAH MELALUI PELAYANAN MODEL CARTER PADA BANK MEGA SYARIAH CABANG KOTA BENGKULU - Rizky Hariyadi (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The purpose of this study was to determine the forms of service of the CARTER model in increasing customer satisfaction at Bank Mega Syariah Bengkulu City Branch. The researcher used a qualitative descriptive approach with the technique of determining the sample using purposive sampling, which consisted of 2 employees and 4 customers. The data collection technique in this study used observation techniques, direct interviews with informants, namely Bank Mega Syariah employees and customers, and documentation. This study uses explanatory data analysis techniques or explanatory explanations or explanations that have a function to describe data with explanations in the form of narratives. From the results of the research and discussion, it was found that the CARTER model according to Othman and Owen which consists of Compliance, Assurance, Realibility, Tangible, Empathy and Responsiveness in increasing customer satisfaction at Bank Mega Syariah Bengkulu City Branch as a whole is quite good in terms of service, but in terms of Tangible it is necessary attention and further improvement of services.